Targeted therapies for autoimmune/idiopathic nonmalignant diseases: risk and management of opportunistic infections - Bavaro, Davide Fiore; Fiordelisi, Deborah; Angarano, Gioacchino; Monno, Laura; Saracino, Annalisa (Expert opinion on drug safety, 2020)
The management of patients affected by autoimmune/idiopathic diseases has been revolutionized by the development of targeted therapies (TT). However, the use of TT is complicated by several adverse events, like opportunistic infections (OIs). The potential of TT to predispose to OIs mainly depends on the site of action; nevertheless, such associations are far from being deterministic, because many factors could increase the infection risk. The impact on the infective risk of different TT used for autoimmune/idiopathic diseases is far from being completely understood. Indeed, many post-marketing reports documented severe or unexpected infections in patients treated with TT that did not emerge during registrative trials. In this review, the authors attempt to provide an easy and practical update about the 'infectious' safety of TT and examine the management strategies of OIs and other infections more frequently observed in the course of treatment with TT. The authors suggest to precisely schedule the clinical management of these subjects, both to prevent and eventually treat promptly the TT-related infectious complications. A coordinated approach should be implemented from different medical specialties to improve the overall understanding of safety of TT and, in general, the management of opportunistic infections in immune-compromised hosts.